Secondary somatosensory and posterior insular cortices: a somatomotor hub for object prehension and manipulation movements - Ishida, Hiroaki; Grandi, Laura Clara; Fornia, Luca (Frontiers in Integrative Neuroscience, 2024)
The manuscript contains 4 figures.• Object grasping-selectivity was weak, with 24 % responding to 3D object fixation. Even nonvisual-responsive neurons showed responses to set-related activity: reaching to grasping neurons were primarily excitatory, whereas holding neurons exhibited inhibitory responses.• SII/pIC neurons encode the entire reach-to-grasp and hold sequences, supporting proximal to distal somatomotor integration during upper limb actions.• Hand-manipulation-related neurons within SII/pIC show a set-related activity possibly playing a role in directing somatomotor attention during action in the absence of visual information from the object.• In summary, SII/pIC may play a role as a somatomotor hub within the lateral grasping network that supports the generation of intentional hand actions based on haptic information.